Modeling and optimization of sound absorption coefficient of microperforated compressed porous metal panel absorber. (September 2020) - Duan, Haiqin; Shen, Xinmin; Yin, Qin; Yang, Fei; Bai, Panfeng; Zhang, Xiaonan; Pan, Ming
Graphical abstract: Abstract: The microperforated compressed porous metal panel (MCPMP) absorber was proposed to develop novel sound absorber with excellent sound absorption performance, fewer utilized materials, and more lightweight. Through treating the compressed porous metal with high compression ratio as microperforated panel, theoretical sound absorption model of the MCPMP absorber was constructed through equivalent circuit approach. Structural parameters of the MCPMP absorber were optimized by cuckoo search algorithm for different target frequency range. The obtained optimal MCPMP absorbers were verified by finite element simulation and validated through standing wave tube measurement. Consistencies among the theoretical data, simulation data, and experimental data proved feasibility and accuracy of theoretical sound absorption model, cuckoo search optimization algorithm, and finite element simulation method. Actual average sound absorption coefficients of the optimal MCPMP absorbers with limited total thickness of 20 mm were 0.4679, 0.7069, and 0.7299 when the target frequency ranges were 100–2000 Hz, 100–4000 Hz, and 100–6000 Hz respectively. By comparison with sound absorption performance of the original porous metal and those of the 10-layer gradient compressed porous metal, effectiveness and practicality of the optimal MCPMP absorber was proved. The developed MCPMP absorber was favorable to enrich the sound absorption theory and promote its practical application.